PERANCANGAN ANTENA MIKROSTRIP UNTUK MENDEKTEKSI PERUBAHAN GULA DARAH SECARA NON-INOVASIF - Putri Indra Wahyuningsih; Levy Olivia Nur; Edwar Edwar (TEKTRIKA, 2022)
Monitoring of glucose levels in the blood often using invasive methods. Blood sampling requires the puncture of a needle on the skin which is used for periodic blood tests over a period of time as a monitor for glucose levels in the blood. This method causes pain, discomfort, and has a risk of irritation/infection. Measurements will be made on three concentrations of glucose, namely hypoglycemia, normal glucose, and hyperglycemia. This technique is based on the relationship of permittivity, and the conductivity of the skin associated with glucose levels in the blood. A narrowband microstrip antenna that works at a frequency of 1,27 GHz. From the measurement results on the tested antenna, it can work at a frequency of 1,27 GHz in off-body and on-body conditions. After simulating the antenna with three glucose concentrations, an analysis was obtained, namely the smaller the Return Loss and VSWR values, the greater the concentration of glucose in the blood. Keywords: antenna, microstrip, glucose, blood glucose level (BGL), narrowband